Effectiveness of Insurance Coverage in Managing Business Interruption Risks in Morocco - Naciri, Rachid (International Journal of Modern Risk Management, 2024)
Purpose: The aim of the study was to examine the effectiveness of insurance coverage in managing business interruption risks in Morocco. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed that while insurance plays a crucial role in mitigating financial losses during disruptions, many businesses remain underinsured or lack adequate coverage tailored to their specific risks. The research highlights that although insurance can provide essential support in recovering from interruptions, the effectiveness is often limited by factors such as insufficient policy limits, lack of awareness among business owners, and gaps in coverage. Unique Contribution to Theory, Practice and Policy: Prospect theory, risk parity theory & behavioral finance theory may be used to anchor future studies of effectiveness of insurance coverage in managing business interruption risks in Morocco. Practically, businesses should focus on several strategies to optimize the effectiveness of their insurance coverage in managing business interruption risks. From a policy perspective, several key recommendations can enhance the effectiveness of insurance coverage in managing business interruption risks.